Development of an Ergonomically – Designed Violin Chinrest Using Additive Manufacturing - John Kenneth J. Barinque; Alshaheen T. Borja; Jeferson C. Cubangbang; Ulysses Ron C. Cruz; Marien P. Teopengco; Marjorie R. Tolentino; Ray Noel M. Delda; Michaela T Espino; Brian J. Tuazon; John Ryan C. Dizon (Universitas PGRI Semarang, 2022)
A violin chinrest is used to ease the pain and prevent injuries of violinists. However, some of them experienced discomfort using normal chinrest. It causes injuries, irritations, and pains that affect the performance of violinists. In that problem, the researcher works toward a goal of not curing the problem but instead avoiding pain, injuries, and discomfort when playing it. A convenience sampling method was used in gathering anthropometric data. The study is limited to the ergonomically designed chin rest itself, which will only be installed at the standard violin size with a length of 60 cm. The designed chinrest is fitted only for the violinists of Jose De Piro Kabataan Orkestra. Three ergonomically designed violin chinrests were produced, which are: side-mounted, semi-centered, and fully centered. The researchers used a paired-samples t-test to compare the means in the results of testing between the normal chinrest and the ergonomically designed chinrest using additive manufacturing. The study concludes that the ergonomically designed violin chinrests using additive manufacturing are light-weight, less expensive, more comfortable to use, and lessen the pain of the violinists based on the overall mean compared to the normal violin chinrest in terms of side-mounted, semi-centered, and centered chinrest.